(untitled) (Research, Society and Development, 2023)
Vascular complications remain an important cause of morbidity, mortality and post-transplantation graft loss, with hepatic artery thrombosis being the most common and its manifestations ranging from the absence of symptoms to the occurrence of septic shock secondary to fulminant hepatic gangrene. Infection is still the leading cause of death after liver transplantation, occurring in most cases within the first month after surgery. Biliary complications are also common causes of morbidity and mortality after liver transplantation, and that their high incidence rate is due to several factors, including ischemia of the biliary tract, immunosuppression, transplantation between individuals of the ABO blood group incompatible, cytomegalovirus infection and technical factors. Immediate postoperative complications may include bleeding, infection, rejection, altered biliary drainage, dehiscence, vascular thrombosis, coagulopathy, portal hypertension, fibrinolysis, hypotension, hypertension, renal dysfunction, psychological alterations, among others. Central pontine myelinolysis (CPM) - non-inflammatory, often symmetrical demyelination concentrated in the center of the pons - has a low incidence in liver recipients, but a high incidence of mortality.